Knee function measured by timed up-and-go test and stair-climbing test after isometric exercise of quadriceps femoris muscles in female patients with knee osteoarthritis - Widjanantie, S C; Tulaar, A BM; Kasjmir, Yoga I; Prasetyo, S B (Indonesian Journal of Rheumatology, 2011)
Background: Osteoarthritis (OA), the most common form of joint disease, can result in long-term disability. Limitation of activity in OA patients may result in a decline in the strength of quadriceps femoris muscles and thus further reduce mobility. Isometric exercise has been known to increase muscle strength, decrease pain, and improve knee function.Objective: To evaluate knee function measured by timed up-and-go test (TUGT) and stair-climbing test (SCT) as well as muscle strength in the fourth and sixth week after isometric exercise of quadriceps femoris muscles and the correlation between these variables.Methods: Female patients with OA underwent isometric exercise of quadriceps femoris muscles 3 times a week for 6 weeks. Muscle strength (measured by tensiometer cable) and knee function (measured by TUGT and SCT) were evaluated before and at week 4and 6 of the exercise.Results: Thirty fi ve female patients were recruited in this study. The majority of the patients (45.7%) were between 60 to 65 years old. Obesity was found in 62.86% of the patients. At week 6, there was significant decrease in mean TUGT and SCT (by 39.0% and 45.6%, respectively; p<0.001), and signifi cant increase in mean right and left quadriceps muscles strength (by 47.9% and 36.7%, respectively; p<0.001). There was a weaknegative correlation (nonsignifi cant) of the increased strength of quadriceps muscles with the increase of knee function according to TUGT (right leg: r = -0.172, p = 0.323; left leg: -0.303, p = 0.077) and SCT (right leg: r = -0.031, p = 0.860); left leg: r = -0.058, p = 0.742).Conclusion: In female patients in this study, significant improvement was found in the strength of quadriceps muscles, TUGT, and SCT after 6 weeks of isometric exercise. There was no signifi cant correlation between muscle strength and knee function according to TUGT and SCT.